Atividade recombinogênica induzida pelo extrato aquoso de pequi (Caryocar brasiliense) em células somáticas de Drosophila melanogaster - Castro, Antônio Joaquim de Souza (2007)
Caryocar brasiliense is a plant popularly known as pequi, native from the Brazilian cerrado , and is widely used in Brazilian cookery. Its fruit presents a high level - carotenes (which is a pro-vitamin A), retinol and vitamin C. These are efficient antioxidizing components, and they scavenging free radicals and prevent mutagenic action of physical and chemical agents. However, in high concentrations it may have mutagenic and recombinogenic effects. So to valuate the genotoxic effects of the pequi we prepared aqueous extracts of pequi (AEP) in concentrations of 1%, 5% and 10%. For this we used the wing spot test in Drosophila melanogaster (Somatic Mutation And Recombination Test SMART). The SMART was fulfilled through the following crossings: 1) standard cross (ST); flare3 virgin females (flr3/TM3, Bds) were crossed with mwh/mwh males; 2) HB High Bioactivation Cross which ORR (ORR, flr3/TM3, Bds) virgin females were crossed with mwh/mwh males. From these crossings, we obtained two kinds of descendents: marked heterozygote (MH - mwh +/+ flr3); balanced heterozygote (BH - mwh +/+TM3, Bds). 72-hour larvae from both crossings were treated with different concentrations of AEP (1%, 5% e 10%). Distilled water and doxorubicin (DXR) (0,125mg/mL) were respectively used as negative and positive controls. The present study aimed the valuating the genotoxic effects of AEP and its antigenotoxic effects against the genotoxic action of DXR (0,125mg/mL). The results obtained demonstrated that AEP induced a statistically significant increase in the frequency of mutant spots, when compared to negative control in all concentrations of HB crossi and only in the concentration of 10 % of ST crossi. In the analysis of HB descendents, we observed a recombinogenic effect of AEP, only when metabolized by P-450. When associated to DXR, there may be an overpotentiality of the genotoxic effect of this chemotherapy. This way, we may conclude that, in these experimental conditions and in the tested concentrations, the aqueous extract of pequi presented a mutagenic and recombinogenic potential.